2014
DOI: 10.1016/j.neuropharm.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of homeostatic synaptic downscaling

Abstract: Homeostatic synaptic downscaling is a negative feedback response to chronic elevated network activity to reduce the firing rate of neurons. This form of synaptic plasticity decreases the strength of individual synapses to the same proportion, or in a multiplicative manner. Because of this, synaptic downscaling has been hypothesized to counter the potential run-away excitation due to Hebbian type of long term potentiation (LTP), while preserving relative synaptic weight encoded in individual synapses and thus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 47 publications
3
59
0
Order By: Relevance
“…This unidirectional role is consistent with a growing literature suggesting that distinct mechanisms underlie homeostatic synaptic strengthening and weakening (reviewed in refs. 53,58). Candidate pathways that may regulate PIKfyve or may be regulated by PIKfyve are mechanisms known to be important for homeostatic synaptic weakening (reviewed in refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unidirectional role is consistent with a growing literature suggesting that distinct mechanisms underlie homeostatic synaptic strengthening and weakening (reviewed in refs. 53,58). Candidate pathways that may regulate PIKfyve or may be regulated by PIKfyve are mechanisms known to be important for homeostatic synaptic weakening (reviewed in refs.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate pathways that may regulate PIKfyve or may be regulated by PIKfyve are mechanisms known to be important for homeostatic synaptic weakening (reviewed in refs. 53,58,87). These include PSD-95, Polo-like kinase 2 (Plk2), cyclin-dependent kinase 5 (CDK5), and L-type voltage-gated calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…These results could suggest the potential for a non-symmetric up-and downregulation, like that observed for LTP and LTD, where potentiation can occur more reliably and quickly [46]. As for experimental evidence for homeostatic downregulation, work in cortical cultures indicates that it is possible [5,20], but approaches for extended increases in activity in vivo remain elusive. The difficulty of maintaining heightened activity in vivo for extended periods of time, may speak to the existence of a fast downregulating homeostatic mechanism that has yet to be experimentally observed.…”
Section: (B) Timescales Of Homeostatic and Hebbian Plasticity Interacmentioning
confidence: 95%
“…Synaptic scaling does have layer-specific properties in cortex, where scaling in layer 4 is limited to early development [7], but layer 5 [12,15] and layer 2/3 [10] can scale throughout adulthood. Numerous molecular mechanisms have been implicated in mediating synaptic scaling, including TNF-alpha [15][16][17], which may be regulated via astrocytic activity and N-methyl-D-aspartate (NMDA) receptor expression [18], retinoic acid [19], among many others (for a review, see [20,21]). Increases in TNF-alpha have been reported to increase and decrease the density of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and gamma aminobutyric acid-A (GABA A ) receptors, respectively, in the plasma membrane [17].…”
Section: Mechanisms Of Homeostatic Stabilizationmentioning
confidence: 99%
“…Indeed, it has been observed that the induction of Homer1a triggers mGluR agonist-independent activity (Ango et al, 2001) and redirects intracellular signaling towards effectors different from those activated by Homer1b/c (Kammermeier and Worley, 2007). Since Homer1a has been described to play a role in synaptic downscaling (Hu et al, 2010;Siddoway et al, 2014) by promoting the hyperpolarization and reducing the activation of the postsynaptic neuron (Errico et al, 2014;Minami et al, 2003;Sylantyev et al, 2013), the reduction of its expression that we observed may represent one of the molecular mechanisms underpinning the elevated glutamatergic tone that has been reported in Ddo −/− mice as a consequence of the persistent elevated D-aspartate levels (Errico et al, 2015).…”
Section: Discussionmentioning
confidence: 99%